Recommendations on Describing the Requirements for Microbiological Quality and Sterility of Medicinal Products - O. V. Gunar (Регуляторные исследования и экспертиза лекарственных средств)
The paper presents recommendations on describing analytical procedures for evaluation of medicinal products in terms of sterility and microbiological quality in accordance with the State Pharmacopoeia of the Russian Federation and the Pharmacopoeia of the EAEU. These quality attributes should be covered in Product specification files for any medicinal product. The paper describes specific considerations for preparation of the corresponding sections of the Russian or EAEU Product specification files. It is necessary to provide and justify quality requirements, refer to or describe the recommended analytical procedure and indicate differences, if any, from the standard one. Standardisation of the approach to microbiological quality control of medicinal products will allow analysts to accurately perform the tests, get reliable results and ensure the safety of medicinal products.